Hybrid Pseudo-Bayesian Estimation in Random Access-Based Tactical FANETs - Kim, Taewook; Lee, Junseong; Jeon, Jimin; Ahn, Jaeha; You, Youngbin; Lee, Min; Yu, Heejung; Lee, Howon (Journal of Korean Institute of Communications and Information Sciences, 2024)
In random access-based tactical flying ad-hoc networks, frequent packet collisions degrade network performance severely. To prevent packet collisions, it is imperative to accurately estimate the number of active UAVs (unmanned aerial vehicles); thus, this paper proposes an estimation method for the number of active UAVs based on pseudo-Bayesian estimation by combining the pure-Bayesian method and the pseudo-Bayesian method. Through intensive simulations, it is confirmed that the proposed method outperforms the various existing methods.
Keywords: Bayesian estimation; Estimation error; Random access; Tactical FANET; UAV